2018
DOI: 10.3390/en11071854
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Asymmetric Gas Distribution on the Instability of a Plane Power-Law Liquid Jet

Abstract: As a kind of non-Newtonian fluid with special rheological features, the study of the breakup of power-law liquid jets has drawn more interest due to its extensive engineering applications. This paper investigated the effect of gas media confinement and asymmetry on the instability of power-law plane jets by linear instability analysis. The gas asymmetric conditions mainly result from unequal gas media thickness and aerodynamic forces on both sides of a liquid jet. The results show a limited gas space will stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…While Newtonian jets appear rigid, non-Newtonian jets have the additional freedom for elastic deformation. Other authors have also reported similar results [20][21][22].…”
Section: Comparison With Other Theoriessupporting
confidence: 72%
See 1 more Smart Citation
“…While Newtonian jets appear rigid, non-Newtonian jets have the additional freedom for elastic deformation. Other authors have also reported similar results [20][21][22].…”
Section: Comparison With Other Theoriessupporting
confidence: 72%
“…where is the liquid normal stress, , is the gas normal stress, and is the pressure induced by the surface tension and it can be expressed as Equation (22).…”
Section: mentioning
confidence: 99%